Giant Inverted Papilloma in the Ureter: An Extremely Rare Urological Condition - AS, Arnob; A, Mahfouz; GK, Banerjee (Archives of Clinical and Medical Case Reports, 2025)
We report a rare case of inverted papilloma in the ureter, in a 75-yearold female who presented with haematuria. During workup, CT and MRI showed filling defect – a soft tissue mass, masquerading as transitional cell carcinoma (TCC) in the right lower ureter. Ureteroscopy showed papillary lesions along the ureter, definitive biopsy could not be obtained due to difficult access. Subsequently on a suspicion of transitional cell carcinoma, nephroureterectomy was performed. Surprisingly, histology confirmed inverted papilloma of the distal ureter, which is an extremely rare to occur in the ureter.